ISU-ISU SYARIAH DALAM KONTRAK DERIVATIF: SATU SOROTAN LITERATUR: Shariah Issues in Derivative Contract: A Literature Review - Nordin, Nadhirah; Ab Rahman, Asmak (Jurnal Syariah, 2011)
Derivatives are a financial instrument that derives its value from underlying asset. This article reviews shariah issues in derivatives contract from the Islamic perspective. Islamic derivatives contract should be free from any elements prohibited by Islam such as riba, maysir (gambling), and gharar (excessive uncertainty). Muslim scholars adopted different approach in discussing the issues of derivatives contract. A study was conducted using data collection method from secondary sources namely journals, seminar proceedings, and books to collect the data comprising scholars’ views in derivatives contract. The data were then analysed using thematic approach. It was found that the difference in opinion among scholars is due to the differences in their understanding and interpretation of al-hadith and in their understanding of derivatives contract itself.